2021
DOI: 10.20947/s0102-3098a0160
|View full text |Cite
|
Sign up to set email alerts
|

Estimaciones de esperanza de vida al nacer en áreas menores de la región pampeana

Abstract: Para determinar el nivel y las diferencias de mortalidad entre los departamentos de Argentina entre 2009 y 2011, aplicamos y comparamos estimaciones de esperanza de vida al nacer en la región pampeana. Usamos tres métodos de suavizado: un enfoque bayesiano, un método de tablas de vida relacional y un enfoque indirecto de los niveles de mortalidad, en los departamentos de la región. Los resultados permiten ordenar los departamentos de las provincias de acuerdo con su esperanza de vida (con intervalos de confian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
2
2
0
Order By: Relevance
“…These associations were stronger among men, a finding that could be driven by certain causes of death and that deserves further exploration. Our findings are also consistent with other research in Argentina describing a negative association between an area-level deprivation index and life expectancy at birth in 32 urban agglomerations,24 and a positive association between mortality rate and unmeet basic needs in Departamentos of the ‘Pampeana’ region 36. Furthermore, these results are consistent with factors associated with within-city inequalities in life expectancy in six large Latin American cities 16…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These associations were stronger among men, a finding that could be driven by certain causes of death and that deserves further exploration. Our findings are also consistent with other research in Argentina describing a negative association between an area-level deprivation index and life expectancy at birth in 32 urban agglomerations,24 and a positive association between mortality rate and unmeet basic needs in Departamentos of the ‘Pampeana’ region 36. Furthermore, these results are consistent with factors associated with within-city inequalities in life expectancy in six large Latin American cities 16…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are also consistent with other research in Argentina describing a negative association between an area-level deprivation index and life expectancy at birth in 32 urban agglomerations, 24 and a positive association between mortality rate and unmeet basic needs in Departamentos of the 'Pampeana' region. 36 Furthermore, these results are consistent with factors associated with withincity inequalities in life expectancy in six large Latin American cities. 16 A key strength of our analyses is that we employed a novel Bayesian approach that draws strength and smooths estimates from surrounding small areas and from the overall structure of the mortality schedule.…”
Section: Discussionsupporting
confidence: 73%
“…Bilal et al [ 13 ] described intraurban variations in LE in six LA cities, including the Buenos Aires metropolitan area (with CABA within), and documented 5.8 and 4.4 years of difference in women’s and men’s LE at birth between the top 90th and bottom 10th percentiles of the metropolitan area of CABA. Sacco et al [ 12 ] reported a significant heterogeneity in LE across departments in the province of Buenos Aires (CABA was not included), showing a 7.6-year gap between departments with the highest and lowest LE at birth. Our findings show that it is possible to reveal and visualize important spatial heterogeneity at a smaller scale within the city.…”
Section: Discussionmentioning
confidence: 99%
“…Challenges for small area estimation (SAE) include the definition and operationalization of what a small area is [ 9 ], statistical noise around death counts with small populations [ 4 , 10 ], and the availability of data, especially given confidentiality concerns [ 11 ]. Previous studies found wide inequities in the distribution of LE for sub-city units in LA countries [ 12 , 13 ]. Although some studies have explored small area variations in LMIC using SAE methods [ 14 , 15 ], there has been little examination of heterogeneity in LE within the rapidly growing cities of LMIC [ 16 ].…”
Section: Introductionmentioning
confidence: 99%